Experimental Validation and Performance Analysis of Flux Switching Permanent Magnet Machines Using the Virtual Current Method for EV/HEV Applications - Shirzad, Ehsan (New Energy Exploitation and Application, 2026)
This paper experimentally validates the Virtual Current Method (VCM) for predicting the air-gap magnetic field and performance of a 12/10 Flux Switching Permanent Magnet (FSPM) machine. Unlike prior VCM studies, which are mainly limited to analytical derivation or numerical verification, this work provides a full experimental assessment using a fabricated FSPM prototype. The prototype was designed based on the proposed analytical model, and a dedicated test bench was developed to measure back-electromotive force (EMF), electromagnetic torque, and air-gap flux density under various load conditions. Experimental measurements are systematically compared with both analytical predictions and 2D finite element method (FEM) simulations. Results show that the VCM-based model predicts the air-gap flux density with a maximum deviation of 3.6% from experiments and 2.8% from FEM. The prototype delivers an average torque of 5.4 N·m at 5 A root mean square (RMS) phase current, achieving a power factor of 0.89 and efficiency above 93%. These findings confirm that the proposed VCM formulation provides a reliable, low-computational-cost, and experimentally validated tool suitable for preliminary design and performance optimization of FSPM machines. The study highlights the practical applicability of VCM, bridging the gap between analytical models and experimental performance evaluation in advanced electric machine design.